Lamotrigine-Loaded Poloxamer-Based Thermo-Responsive Sol-Gel: Formulation, In Vitro Assessment, Ex Vivo Permeation, and Toxicology Study - Riaz, Maria (2023)
The present study aimed to prepare, characterize, and evaluate a thermo-responsive sol-gel for intranasal delivery of lamotrigine (LTG), which was designed for sustained drug delivery to treat epilepsy. LTG sol-gel was prepared using the cold method by changing the concentrations of poloxamer 407 and poloxamer 188, which were used as thermo-reversible polymers. The optimized formulations of sol-gel were analyzed for clarity, pH, viscosity, gelation temperature, gelation time, spreadability, drug content, in vitro drug release studies, ex vivo permeation studies, and in vivo toxicological studies. FTIR, XRD, and DSC were performed to determine the thermal stability of the drug and polymers. The prepared formulations had a clear appearance in sol form; they were liquid at room temperature and became gel at temperatures between 31 °C and 36 °C. The pH was within the range of the nasal pH, between 6.2 and 6.4. The drug content was found to be between 92% and 94%. In vitro drug release studies indicated that the formulations released up to 92% of the drug within 24 h. The FTIR, DSC, and XRD analyses showed no interaction between the drug and the polymer. A short-term stability study indicated that the formulation was stable at room temperature and at 4-8 °C. There was a slight increase in viscosity at room temperature, which may be due to the evaporation of the vehicle. A histological study indicated that there were no signs of toxicity seen in vital organs, such as the brain, kidney, liver, heart, and spleen. It can be concluded from the above results that the prepared intranasal sol-gel for the delivery of LTG is safe for direct nose-to-brain delivery to overcome the first-pass effect and thus enhance bioavailability. It can be considered an effective alternative to conventional drug delivery for the treatment of epilepsy.